2012
DOI: 10.1007/s00228-012-1315-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carboxylesterase 1 (CES1) polymorphisms on the pharmacokinetics of oseltamivir in humans

Abstract: In our study, the known interindividual variability in oseltamivir metabolism was not explained by CES1A genetic polymorphisms, but are likely the result of other factors. While one subject was found to exhibit an approximate tenfold higher AUC than the other subjects, no abnormal behaviors were associated with the increased oseltamivir plasma concentrations. Further studies are required to reveal the cause of individual differences in CES1A metabolism and the abnormal behavioral effects of oseltamivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
3
25
1
Order By: Relevance
“…CES enzymes hydrolyze diverse xenobiotic and endogenous substrates that contain carboxylic acid esters, carbamates, thioesters, and amide compounds. [1][2][3][4] Two major subfamilies of identified CES are human carboxylesterase 1 (CES1) and human carboxylesterase 2 (CES2). [2,4] CES1 gene is located on chromosome 16q13-q22.1 and contains 14 exons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CES enzymes hydrolyze diverse xenobiotic and endogenous substrates that contain carboxylic acid esters, carbamates, thioesters, and amide compounds. [1][2][3][4] Two major subfamilies of identified CES are human carboxylesterase 1 (CES1) and human carboxylesterase 2 (CES2). [2,4] CES1 gene is located on chromosome 16q13-q22.1 and contains 14 exons.…”
Section: Introductionmentioning
confidence: 99%
“…[2,4] CES1 gene is located on chromosome 16q13-q22.1 and contains 14 exons. [3,5] To date (29-Apr-2014), a total of 1107 single nucleotide polymorphisms (SNPs) in CES1 have been documented in the NCBI SNP database (http://www.ncbi. nlm.nih.gov).…”
Section: Introductionmentioning
confidence: 99%
“…CES1 has been previously biochemically characterized as an oseltamivir-activating enzyme, yet human CES1 polymorphisms do not account for all of the variability in patient prodrug activation 27 . Under the background of this model, we sought to establish if substrate-competitive activity-based profiling could directly annotate oseltamivir-activating enzymes among serine hydrolases present in human Caco-2 cell homogenates, a cell line that expresses multiple carboxylesterases 28 and is widely used for modeling human intestinal absorption 29 .…”
Section: Substrate-competitive Profiling Of Oseltamivir-binding Serinmentioning
confidence: 99%
“…The formation of sacubitrilat from sacubitril is mediated by carboxylesterase 1, an enzyme which is shown to have distinct ethnic differences based on genetic polymorphisms and haplotype frequencies [96]. However, these differences did not impact its activity, measured as the ratio of oseltamivir carboxylate/oseltamivir, a carboxylesterase 1-mediated conversion [97]. Our pooled analysis, which revealed no clinically relevant impact of race and ethnicity on pharmacokinetics of sacubitril and sacubitrilat, also suggested that carboxylesterase 1 polymorphisms are unlikely to affect the conversion of sacubitril to sacubitrilat.…”
Section: Race/ethnicitymentioning
confidence: 99%